Analysis of the prevalence, secretion and function of a cell cycle-inhibiting factor in the melioidosis pathogen Burkholderia pseudomallei. - Pornpan Pumirat; Charles Vander Broek; Niramol Juntawieng; Veerachat Muangsombut; Pattarachai Kiratisin; Kovit Pattanapanyasat; Joanne M Stevens; Mark P Stevens; Sunee Korbsrisate (PLoS ONE)
Enteropathogenic and enterohaemorrhagic Escherichia coli express a cell cycle-inhibiting factor (Cif), that is injected into host cells via a Type III secretion system (T3SS) leading to arrest of cell division, delayed apoptosis and cytoskeletal rearrangements. A homologue of Cif has been identified in Burkholderia pseudomallei (CHBP; Cif homologue in B. pseudomallei; BPSS1385), which shares catalytic activity, but its prevalence, secretion and function are ill-defined. Among 43 available B. pseudomallei genome sequences, 33 genomes (76.7%) harbor the gene encoding CHBP. Western blot analysis using antiserum raised to a synthetic CHBP peptide detected CHBP in 46.6% (7/15) of clinical B. pseudomallei isolates from the endemic area. Secretion of CHBP into bacterial culture supernatant could not be detected under conditions where a known effector (BopE) was secreted in a manner dependent on the Bsa T3SS. In contrast, CHBP could be detected in U937 cells infected with B. pseudomallei by immunofluorescence microscopy and Western blotting in a manner dependent on bsaQ. Unlike E. coli Cif, CHBP was localized within the cytoplasm of B. pseudomallei-infected cells. A B. pseudomallei chbP insertion mutant showed a significant reduction in cytotoxicity and plaque formation compared to the wild-type strain that could be restored by plasmid-mediated trans-complementation. However, there was no defect in actin-based motility or multinucleated giant cell formation by the chbP mutant. The data suggest that the level or timing of CHBP secretion differs from a known Bsa-secreted effector and that CHBP is required for selected virulence-associated phenotypes in vitro.